Programmable Nanoassemblies from Non‐Assembling Homopolymers Using Ad Hoc Electrostatic Interactions. Issue 15 (13th March 2017) - Zhuang, Jiaming; Garzoni, Matteo; Torres, Diego Amado; Poe, Ambata; Pavan, Giovanni M.; Thayumanavan, S.
Abstract: Robust nanostructures were obtained from polymers that otherwise do not assemble by using a novel approach based on electrostatic self‐assembly. The essence of this strategy involves the use of divalent counterions to temporarily perturb the packing features of the ionic groups in a homopolymer, which results in a vesicle‐like structure that is captured in situ through a simple crosslinking reaction. The fidelity of the assembly has been tested for molecular transport across the nanomembrane, both for the molecules encapsulated in the lumen and for those trapped in the membrane itself. The membranes are addressable for robust multifunctionalization of their surfaces and for tunable transmembrane molecular transport. Abstract : Multivalent counterions can be utilized to transform a non‐assembling homopolymer into a programmable nanoassembly with tunable interfacial and transport properties. The counterions temporarily perturb the packing features of the ionic groups in the homopolymer, which results in vesicle‐like structures.